Consumer Legal Protection in E-Commerce Transactions: A Case Study of Grab Toko Platform. - Wibowo, Elang; Retno Mumpuni, Niken Wahyuning (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
This research aims to analyze how technology has facilitated many activities in society, particularly in the economic sector through the use of the internet, and to explore the risks and legal protections for consumers in e-commerce transactions in Indonesia. The absence of previous research specifically examining the relationship between technology, e-commerce, and consumer protection underscores the novelty of this study in the context of normative law. The research method used is normative legal research, relying on secondary data analysis involving legal interpretation. The findings show that the internet supports increased revenue, cost savings, advertising, marketing, and customer service. However, e-commerce platforms such as Tokopedia and Grab Toko also pose risks of consumer rights violations. A case study of Grab Toko revealed fraud that harmed consumers due to undelivered orders. Consumer legal protection is regulated under Law Number 8 of 1999, which emphasizes the responsibility of businesses to provide clear and honest information and to resolve disputes fairly. This study examines the effectiveness of legal protection for e-commerce consumers, focusing on the Grab Toko case involving false information and fraud. The findings indicate that consumer rights violations still occur, and legal protections need to be strengthened to protect consumers from harm.